Fixed to VoIP Interconnection: Regulation with Asymmetric Termination Costs - Torben Stühmeier (International Telecommunications Society (ITS), 2010)
Typically, incumbent providers enjoy a demand-side advantage over any entrant. However, market entrants may enjoy a supply-side advantage in costs over the incumbent, since they are more efficient or operate on innovative technologies, such as the voice of internet protocol (VoIP) telephony. Regulation with a supply-side asymmetry has rarely been addressed. Considering both a supply-side and a demand- side asymmetry, the present model analyzes the effects different regulation regimes. Regulation may have adverse effects on subscribers, market shares, and profits. If providers can discriminate between on-net and off-net prices, asymmetric regulation has no local effect on market shares, independent of any demand- and supply-side asymmetry. Otherwise, with reciprocal termination charges, price discrimination leads to qualitatively same effects than nondiscriminatory pricing.
Keywords: L13; L51; L96; 330; Termination charges; Interconnection; Regulation; Price Discrimination; Voice over Internet Protocol (VoIP)